The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1093/europace/eur269
|View full text |Cite
|
Sign up to set email alerts
|

Trans-venous lead removal without the use of extraction sheaths, results of >250 removal procedures

Abstract: Lead removal using manual traction, without the assistance of lead extraction sheaths, is clinically successful in ~85% of the lead extraction procedures. Concomitant morbidity and mortality are low. The highest clinical success (~95%) was observed in patients with leads implanted less than 2.6 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Those leads were more likely to be defibrillating leads, due to their stiffness and resistance to extension and breaking. The percentage of such leads in the study group was small, whereas de Bie et al [23] reported the (82%) efficacy of direct traction in large group of patients with electrodes implanted for up to 84 months [19,24]. The connective tissue, which binds the leads to the wall of the vessel, heart or the valve apparatus, is not formed evenly in all patients.…”
Section: Discussionmentioning
confidence: 92%
“…Those leads were more likely to be defibrillating leads, due to their stiffness and resistance to extension and breaking. The percentage of such leads in the study group was small, whereas de Bie et al [23] reported the (82%) efficacy of direct traction in large group of patients with electrodes implanted for up to 84 months [19,24]. The connective tissue, which binds the leads to the wall of the vessel, heart or the valve apparatus, is not formed evenly in all patients.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, the safety threshold percentiles may assist physicians in determining the right balance between lead replacement at the time of generator change and the undersensing risk of VF during follow-up. Lead removal is not exempt from life-threatening complications and such a decision is especially difficult in patients with chronically low BR R-wave amplitudes 20. Our data suggest that chronically low BR R-wave amplitudes may be stable.…”
Section: Discussionmentioning
confidence: 80%
“…Another limitation of this study is that all patients were considered suitable for defibrillation with an S-ICD. Although current data do not indicate that there is a proportion of patients not suitable for defibrillation using this new device, it should be acknowledged that this issue should be explored in more detail in future studies 6 25 26. Furthermore, in the current study, CRT-D implantation was done according to the then existing guidelines, and therefore changes in these guidelines could not be accounted for.…”
Section: Discussionmentioning
confidence: 87%